The Managerial Skills and It`s Role in Strengthening the Competitive Edge of Companies: A Case Study in the General Company for Construction Industries (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This research tries to reveal how to manage and control the competitive edge for business by building managerial skills in various organizational levels. Our research aims at finding out the nature of various technical, human and in tellectual skills of a new president whose superiority is his competitive ness in the application field at general company for construe tioual  industriesand testing the surveyed minor and major changes through a questionnaire to collect information from officials. The sample was composed of (45) director. The data was analyzed  using some methods and statistical programs. The most prominent of these is (SPSS) that was used to extract the arithmetic mean, standard deviation, correlation coefficient (F) and (R2) in order to obtain the targeted results. The research concluded that managerial skills directly influence the level of competitive edge of the company and produce unique competitive advantage that make it difficult for competitors to emulate. The researcher develop a set of scientific recommendations that attention should be paid for administrative skills without neglecting human skills that enhance the link between top and lower levels of management.